(untitled) (Clinics, 2005)
BACKGROUND: Progress testing is a longitudinal tool for evaluating knowledge gains during the medical school years. OBJECTIVES: (1) To implement progress testing as a form of routine evaluation; (2) to verify whether cognitive gain is a continuous variable or not; and (3) to evaluate whether there is loss of knowledge relating to basic sciences in the final years of medical school. METHODS: A progress test was applied twice a year to all students from 2001 to 2004. The mean percentage score was calculated for each school year, employing ANOVA with post hoc Bonferroni test evaluation for each test. RESULTS: Progress testing was implemented as a routine procedure over these 4 years. The results suggest a cognitive gain from first to sixth year in all eight tests, as a continuum (P for trend < .0001). Gain was found to be continuous for basic sciences (taught during the first 2 years), clinical sciences (P < .0001), and clerkship rotation (P < .0001). There was no difference between the performance of men and women. CONCLUSION: Progress testing was implemented as a routine, applied twice a year. Data suggest that cognitive gain during medical training appears to be a continuum, even for basic science issues.